Immunological Impact of a Gluten-Free Dairy-Free Diet in Children With Kidney Disease: A Feasibility Study - Pérez-Sáez, María José; Uffing, Audrey; Leon, Juliette; Murakami, Naoka; Watanabe, Andreia; Borges, Thiago J.; Sabbisetti, Venkata S.; Cureton, Pamela; Kenyon, Victoria; Keating, Leigh; Yee, Karen; Fernandes Satiro, Carla Aline; et al. (Frontiers in Immunology, 2021)
Kidney disease affects 10% of the world population and is associated with increased mortality. Steroid-resistant nephrotic syndrome (SRNS) is a leading cause of end-stage kidney disease in children, often failing standard immunosuppression. Here, we report the results of a prospective study to investigate the immunological impact and safety of a gluten-free and dairy-free (GF/DF) diet in children with SRNS. The study was organized as a four-week summer camp implementing a strict GF/DF diet with prospective collection of blood, urine and stool in addition to WES of DNA of participants. Using flow cytometry, SOMAscan and microbiome metagenomics, we show that GF/DF diet had a major anti-inflammatory effect in all participants both at the protein and cellular level with 4-fold increase in Treg/Th17 ratio and the promotion of a favorable regulatory gut microbiota. Overall, GF/DF can have a significant anti-inflammatory effect in children with SRNS and further trials are warranted to investigate this potential dietary intervention in children with SRNS.